Level Berpikir Probabilistik Siswa SMPN 4 Kepanjen - Arini Mayan Fa'ani; Ulfa Masamah; Marhayati Marhayati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to classify student responses in dealing with probabilistic problems according totheir level, analyze, and identify indicators at each level. This study used a descriptivequalitativeapproach with data collection techniques in the form of tests and interviews which were tested on 66 seventh grade students as research subjects. The results showed that 28 students were at the subjective level, 30 students were at the transitional level, and 8 students were at the informal quantitative level, and no students were at the numerical level. In addition, there are additional indicators at the subjective and transitional levels. Meanwhile, at the informal quantitative level, there are no additional indicators.Keywords: probabilistic thinking